Studies on the regulation of solvent production and endospore formation in Clostridium Acetobutylicum P262 - Long, Susan (Department of Molecular and Cell Biology, 2017)
The aim of this study was to characterise the relationships between solventogenesis and endospore formation in Clostridium acetobutylicum strain P262. Growth and endospore formation was monitored in a number of complex and minimal media and as a result of these studies a new defined sporulation medium was developed. The defined system produced high levels of solvents and supported 60 80% sporulation in C. acetobutylicum P262. Endospore formation occurred near-synchronously, enabling this system to be used in correlative physiological and morphological studies. Five other Type Culture Clostridium strains grew and sporulated less well in the C. acetobutylicum minimal medium (CAMM). These variations emphasise the importance of strain differences amongst the Clostridia. Two well defined physiological phases, the acidogenic phase and the solventogenic phase, which characterise the industrial ABE fermentation process were observed in CAMM.